Impact of Corporate Social Responsibility on the Effectiveness of Companies' Business Activities - Marina V. Vasiljeva; Alexander N. Semin; Vadim V. Ponkratov; Nikolay V. Kuznetsov; Evgeniy V. Kostyrin; Nadezhda N. Semenova; Marina I. Ivleva; Angelina O. Zekiy; Natalia V. Ruban-Lazareva; Alexander L. Elyakov; Iskandar Muda (Ital Publication, 2023)
Background: Corporate social responsibility (CSR) has a great influence on the sustainability of company development, so it can be considered a business model for business effectiveness. Objective: The objective of the research is to determine the mutual influence of real-estate companies’ activities and CSR effectiveness in different countries. This study examines indicators for assessing companies’ financial stability, CSR, and working capital management's influence on the activity effectiveness of real-estate companies. Methods/Analysis: Questionnaires, the principal component method, the Sobel test, and linear regression analysis are used to evaluate the relationship between CSR and the business performance of autocratic management-style companies. The authors’ algorithm for assessing a company’s financial stability, CSR, and capital management, which affect the efficiency of companies, is proposed. Findings: Empirical analysis has shown that management has no mediating effect on CSR and enterprise performance relationships for companies with high financial stability and working capital, though it has a stimulating effect for low financial stability companies. CSR and business performance have positive relationships in companies, but despite financial stability growing, the autocratic leadership style reduces interest in CSR development. This paper conceptualizes the impacts of CSR on the effectiveness of companies. Novelty: The novelty of this study is to create theoretical and practical provisions aimed at laws and regulations. Doi: 10.28991/ESJ-2023-07-03-08 Full Text: PDF